Waste plastic regenerated sprayed concrete and preparation method thereof
By using plastic particles with interconnected pores in sprayed concrete and optimizing aggregate grading, the problems of over-exploitation of natural ore resources and limited application of waste plastics are solved, achieving high strength, low rebound rate and resource recycling effects.
Patent Information
- Application Number
- CN202411960606.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing sprayed concrete uses natural ore and river sand as aggregates, resulting in excessive mining of ore resources and environmental pollution. At the same time, waste plastics are limited in their application in concrete due to their low strength and poor adhesion to cement.
Plastic particles with interconnected pores formed by plastic strips through interlaced winding are used as fine aggregates, and the pores are filled with cement slurry to improve adhesion, and the grading and addition of coarse and fine aggregates are optimized to improve the structural strength and fluidity of concrete.
It effectively improves the structural strength and adhesion of concrete, reduces rebound rate and waste, realizes the recycling and utilization of resources, and reduces dependence on natural ores.
Smart Images

Figure CN119750993A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste plastic treatment, and more specifically, relates to a waste plastic recycled shotcrete and a preparation method thereof. Background Art
[0002] With the development of economic construction and urbanization, the scale of infrastructure construction is huge, and the demand for concrete is also increasing day by day. At present, the coarse and fine aggregates used in the preparation of shotcrete are mostly natural ores and natural river sand, but there are many problems with the use of natural sand and gravel resources, such as high transportation costs, long construction period, and the limited amount of natural sand and gravel after all. It is obviously not a long-term solution to blindly consume a large amount of natural resources. Excessive exploitation of natural sand and gravel can easily lead to a series of problems such as resource scarcity, environmental pollution, and barren land.
[0003] At the same time, there are many problems with machine-made sand made from mined rocks. There may be too many particles larger than 2.5mm and smaller than 0.08mm in the machine-made sand, which will affect the workability and strength of the concrete. Poorly graded machine-made sand may cause the bond between cement paste and aggregate in concrete to decrease, thereby increasing the rebound rate of shotcrete. Therefore, it is urgent to find a reasonable, economical and environmentally friendly material to replace natural aggregates, which can not only solve the problem of over-exploitation of ore resources, but also realize the recycling of resources.
[0004] At present, the output of waste plastics is huge, causing waste of land resources and soil pollution, and even air and water pollution. Therefore, it is very important to find a suitable way to recycle waste plastics.
[0005] Since waste plastics are light, low-cost, and chemically stable, using waste plastic particles instead of concrete aggregates in shotcrete can reduce the weight of concrete, making it easier to spray. However, waste plastics are not widely used to replace concrete aggregates. There are several reasons for this: 1. Low strength: Compared with aggregates such as sand and stone, the compressive strength of plastic itself is low, and its use in concrete will also reduce the compressive strength of concrete; 2. Poor adhesion with cement: The surface of plastic material is smoother than natural aggregate, so it has poor adhesion with cement hydration products, resulting in reduced concrete strength; 3. Irregular shape: Natural aggregates are weathered in nature, mostly oval or round and without edges and corners, while the particles formed by crushing waste plastics are mostly irregular in shape and have many edges and corners, which is not conducive to the compactness of concrete. Summary of the invention
[0006] The purpose of the present invention is to provide a waste plastic recycled shotcrete and a preparation method thereof, so as to solve the technical problems that the existing shotcrete usually uses natural ore and natural river sand as aggregates, resulting in over-exploitation of ore resources; and the waste plastic has low strength and poor adhesion with cement, which limits its application in concrete.
[0007] In order to achieve the above object, the technical solution provided by the present invention is:
[0008] The present invention provides a waste plastic recycled shotcrete, the raw materials of which include cement, coarse aggregate and fine aggregate, wherein the fine aggregate part uses plastic granules, which are hollow structures with interconnected pores formed by plastic strips, and the pores connect the outside of the granules with the inside thereof.
[0009] Since the plastic particles are lighter, they will produce smaller rebound when they collide with the spraying surface during spraying, which is conducive to reducing the rebound rate of sprayed concrete, thereby reducing waste. At the same time, the lightweight characteristics of plastic also make it more convenient to transport and less costly. Therefore, it is very feasible to replace concrete aggregate with waste plastic. At present, there are studies on the use of waste plastic to replace the natural aggregate in existing concrete, but due to the relatively low strength of plastic and poor adhesion to cement, its wide application is limited. However, the present application optimizes the structure of the plastic granule body, and the plastic granule body is a structure with interconnected internal pores formed by plastic strips through staggered winding and the like, and the above-mentioned pores connect the outside and the inside of the granule body, so that cement can flow and fill into the above-mentioned pores, so that the plastic granule body and the cement hydration product are mutually penetrated to form a whole, and then on the one hand, the overall structural strength of the concrete can be effectively improved, and on the other hand, the problem of poor adhesion between conventional granular plastic bodies and cement hydration products can be solved, so the plastic granule body can be used to replace part of the natural fine aggregate to overcome the gradation defects of the natural fine aggregate.
[0010] It should be noted that the specific structural shape of the plastic granules is not limited in the present application, as long as the granules are interconnected with each other and are also connected with the outside of the granules so that cement can penetrate and fill the pores therein. For example, the plastic granules can be a wavy multi-layer stacked hollow structure as a whole, or a porous spherical structure formed by a plurality of plastic strips intertwined and wound with each other (for example, the pores are connected in a honeycomb distribution).
[0011] According to the shotcrete described in any technical solution of the present invention, the mass of plastic particles in the fine aggregate accounts for 10% to 20% of the total amount of fine aggregate, thereby preventing excessive addition of plastic particles from causing adverse effects on the overall structural strength and other performance of concrete.
[0012] According to the shotcrete described in any technical solution of the present invention, the porosity of the plastic particles reaches 5% to 20%, thereby ensuring the overall structural strength of the obtained concrete and effectively improving the bonding performance between the plastic particles and cement hydration products.
[0013] According to the shotcrete described in any technical solution of the present invention, the particle size of the coarse aggregate is 5mm-10mm, the fine aggregate includes particles with a particle size of less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm, and the mass proportions of the fine aggregate with a particle size of less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm are 30%-35%, 45%-50%, and 20%-25%, respectively, and it is further preferred that the mass ratio of the three particle sizes is 3:5:2. By optimizing the particle gradation between aggregates of different particle sizes, the structural strength of the obtained concrete can be further guaranteed.
[0014] According to the shotcrete described in any technical solution of the present invention, the fine aggregate includes plastic particles and machine-made sand, and the addition amount and particle size distribution of the plastic particles are determined according to the grading defects of the recycled coarse aggregate and the machine-made sand.
[0015] According to the shotcrete described in any technical solution of the present invention, the coarse aggregate includes recycled coarse aggregate, and plastic particles can also be used to replace part of the recycled coarse aggregate. According to the particle size grading defects of the recycled coarse aggregate and the machine-made sand, plastic particles of a specific particle size range and quality are added, thereby effectively solving the problem that the workability and strength of the concrete are affected by the grading defects of the existing recycled coarse aggregate and the machine-made sand, and ensuring the bonding force between the cement paste and the aggregate in the concrete, and increasing the rebound rate of the shotcrete. It is further preferred that the mass ratio of the recycled coarse aggregate and the plastic particles in the coarse aggregate is (4 to 9): 1, thereby effectively ensuring the structural strength of the recycled concrete. The recycled coarse aggregate is further preferably recycled concrete or granite.
[0016] According to the shotcrete of any technical solution of the present invention, the total amount of coarse aggregate and fine aggregate in the concrete is 1700-1800 kg / m 3 , and the mass of fine aggregate accounts for 45% to 55% of the total amount of aggregate (fine aggregate + coarse aggregate).
[0017] According to the shotcrete described in any technical solution of the present invention, the cement is ordinary Portland cement, and its dosage is 400-500kg / m 3 And / or the concrete is also added with a water reducing agent to adjust the fluidity of the concrete, the dosage of which is 6.8kg / m 3 ~7.8kg / m 3; and / or the concrete is further added with an accelerating agent, the dosage of the accelerating agent is 30-38kg / m 3 ; and / or the water content in concrete is 150-200kg / m 3 By optimizing the amount of water reducing agent and / or accelerating setting agent added, the fluidity of concrete can be effectively guaranteed. It should be noted that the types of the water reducing agent and accelerating setting agent are not limited, and existing water reducing agents and accelerating setting agents for concrete can be directly used. For example, the water reducing agent can be a polycarboxylic acid water reducing agent, a naphthalene water reducing agent, etc.
[0018] According to the sprayed concrete of any technical solution of the present invention, a thickener is also added to the concrete, and the thickener is preferably industrial grade polyacrylamide, and the dosage is 0.01 kg / m 3 ~0.03kg / m 3 Since plastic particles do not absorb water, it is easy to cause water seepage in concrete, uneven distribution of plastic, and floating in concrete. Therefore, by optimizing the structure of plastic particles and using the above-mentioned specific types of thickeners, the above situation can be effectively improved to ensure the uniform distribution of plastic in concrete. The molecular weight of the polyacrylamide is further preferably 1.2×10 7 Meanwhile, other components or admixtures may be added to the concrete as required.
[0019] According to the shotcrete described in any technical solution of the present invention, the one-day compressive strength of the concrete is 25-37Mpa, and the 28-day compressive strength is 40-70Mpa.
[0020] The present invention also provides a method for preparing the waste plastic recycled shotcrete, comprising: stirring and mixing raw materials containing cement, coarse aggregate and fine aggregate in water evenly, the stirring time is preferably not less than 3 minutes, and during the stirring process, cement slurry is filled into the pores of the plastic particles to form a whole with the plastic particles and the concrete.
[0021] According to the preparation method described in any technical solution of the present invention, plastic particles are used to replace part of the recycled coarse aggregate, and the mass ratio of the recycled coarse aggregate to the plastic particles in the coarse aggregate is (4-9):1.
[0022] In summary, the technical solution provided by the present invention can achieve the following beneficial effects compared with the prior art:
[0023] (1) The present invention optimizes the structure of plastic particles to form interconnected pores inside the particles, so that cement slurry can be filled into the pores, thereby effectively improving the structural strength of concrete and improving the adhesion between the plastic particles and the cement slurry. Therefore, the present invention can replace part of the natural fine aggregate, overcome the grading defects of natural aggregate, and solve the problem in the prior art that plastics cannot be widely used in concrete due to their low strength and poor adhesion with cement slurry.
[0024] (2) The present invention further optimizes the addition amount of coarse aggregate and fine aggregate (especially plastic particles) and the particle size distribution, as well as the porosity of the plastic particles, so as to further ensure the overall structural strength and workability of the concrete and the bonding strength between the aggregate and the cement paste.
[0025] (3) The present invention optimizes the types and addition amounts of water reducers and thickeners, thereby effectively ensuring the fluidity of concrete and improving the distribution uniformity of plastic particles in concrete, thereby ensuring the performance of concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the structure of plastic particles according to an embodiment of the present invention.
[0027] In the figure: 1. Plastic particles; 2. Cement slurry. DETAILED DESCRIPTION
[0028] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with specific embodiments.
[0029] Example 1
[0030] The waste plastic recycled shotcrete of this embodiment comprises ordinary Portland cement, coarse aggregate, fine aggregate, water reducer and thickener as raw materials, wherein the coarse aggregate is recycled coarse aggregate (specifically recycled concrete) with a particle size of 5mm-10mm, and the fine aggregate comprises plastic particles and machine-made sand, wherein the plastic particles are hollow structures with interconnected pores formed by a plurality of plastic strips, and the pores connect the outside of the particles with the inside, and the porosity of the plastic particles is 20%.
[0031] Specifically, the water reducer in this embodiment is polycarboxylate water reducer, and its dosage is 7.3kg / m 3 The thickener is industrial grade polyacrylamide (molecular weight 1.2×10 7 ), the dosage is 0.02kg / m 3 , cement content 488kg / m 3 , water content 164kg / m 3In this example, the total amount of coarse aggregate and fine aggregate is 1728 kg / m 3 The mass ratio of fine aggregate to coarse aggregate is 51:49, and the fine aggregate includes particles with a particle size of less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm. The mass ratio of the fine aggregate with a particle size of less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm in this embodiment is 3:5:2, and the fine aggregate with a particle size of less than 0.5mm and a particle size of 2mm-5mm are all machine-made sand, and the fine aggregate with a particle size of 0.5mm-2mm is mixed by the plastic particles and machine-made sand in a mass ratio of 1:4.
[0032] The preparation method of shotcrete of this embodiment is to add some plastic particles with a particle size of 0.5mm-2mm as fine aggregate according to the particle size gradation defects of recycled coarse aggregate and machine-made sand, mix and stir the raw materials evenly, and the stirring time is not less than 3 minutes, so that the cement slurry is filled into the plastic particles during stirring, so that the plastic particles and concrete form a whole, and finally the waste plastic recycled shotcrete of this embodiment is obtained. The one-day compressive strength of the concrete obtained in this embodiment is 35Mpa, and the 28-day compressive strength is 65MPa.
[0033] Example 2
[0034] A waste plastic recycled shotcrete of this embodiment, whose raw materials include ordinary Portland cement, coarse aggregate, fine aggregate, water reducer and thickener, wherein the coarse aggregate is recycled coarse aggregate (specifically recycled concrete), and its particle size is 5mm-10mm, and the fine aggregate includes plastic granules and machine-made sand, and the above-mentioned plastic granules are hollow structures with interconnected pores formed by multiple plastic strips, and the pores connect the outside of the granules with the inside. Specifically, the plastic granules in this embodiment are hollow spherical structures with interconnected pores formed by the interlaced winding of plastic strips, and the porosity of the plastic granules is 15%.
[0035] In this embodiment, the water reducer is a naphthalene-based water reducer, and its dosage is 6.8 kg / m 3 kg / m 3 The thickener is industrial grade polyacrylamide (molecular weight 1.2×10 7 ), the dosage is 0.01kg / m 3 kg / m 3 , cement content 500kg / m 3 , water content 200kg / m 3 In this embodiment, the total amount of coarse aggregate and fine aggregate is 1700 kg / m 3, wherein the mass proportion of fine aggregate is 45%, and the fine aggregate includes particles with a particle size of less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm. In the fine aggregate of this embodiment, the mass proportions of particle sizes less than 0.5mm, 0.5mm-2mm, and 2mm-5mm are 35%, 45%, and 20% respectively, and the fine aggregates with a particle size of 0.5mm-2mm and 2mm-5mm are all machine-made sand, and the fine aggregate with a particle size less than 0.5mm is a mixture of plastic particles and machine-made sand, wherein the mass of the plastic particles accounts for 15% of the total amount of fine aggregate.
[0036] The preparation method of shotcrete of this embodiment is to add some plastic particles with a particle size of less than 0.5 mm as fine aggregate according to the particle size gradation defects of recycled coarse aggregate and machine-made sand, mix and stir all the raw materials together for not less than 3 minutes, fill the cement slurry into the plastic particles during stirring, and make the plastic particles and concrete form a whole, and finally obtain the waste plastic recycled shotcrete of this embodiment (such as Figure 1 The figure shows a schematic diagram of cement paste 2 filling the internal voids of plastic particles 1). The one-day compressive strength of the concrete obtained in this embodiment is 32 MPa, and the 28-day compressive strength is 58 MPa.
[0037] Example 3
[0038] The waste plastic recycled shotcrete of this embodiment has the same raw material composition as that of embodiment 2, except that the amount of water reducer in this embodiment is 7.8 kg / m 3 The dosage of thickener is 0.03kg / m 3 , cement content 400kg / m 3 , water content 150kg / m 3 The coarse aggregate in this embodiment is recycled coarse aggregate (specifically recycled granite), with a particle size of 5mm-10mm, and the total amount of coarse aggregate and fine aggregate is 1800kg / m 3 The mass proportion of fine aggregate is 55%, and the fine aggregate includes particles with a particle size less than 0.5mm, a particle size between 0.5mm-2mm, and a particle size between 2mm-5mm.
[0039] The mass proportions of the fine aggregates with particle sizes less than 0.5 mm, 0.5 mm-2 mm, and 2 mm-5 mm in this embodiment are 31%, 45%, and 24% respectively, and the fine aggregates with particle sizes less than 0.5 mm and 0.5 mm-2 mm are all machine-made sand, and the fine aggregates with particle sizes of 2 mm-5 mm are a mixture of plastic particles and machine-made sand, in which the mass of the plastic particles accounts for 20% of the total amount of fine aggregate.
[0040] The preparation method of shotcrete of this embodiment is to add some plastic particles with a particle size of 2mm-5mm as fine aggregate according to the particle size gradation defects of recycled coarse aggregate and machine-made sand, mix and stir the raw materials evenly, and the stirring time is not less than 3 minutes, so that the cement slurry is filled into the plastic particles during stirring, so that the plastic particles and concrete form a whole, and finally the waste plastic recycled shotcrete of this embodiment is obtained. The one-day compressive strength of the concrete obtained in this embodiment is 28Mpa, and the 28-day compressive strength is 55MPa.
[0041] Example 4
[0042] The waste plastic recycled shotcrete of the present embodiment comprises ordinary Portland cement, coarse aggregate, fine aggregate, water reducer, thickener and accelerator, wherein the coarse aggregate is recycled coarse aggregate with a particle size of 5 mm-10 mm, and the fine aggregate comprises plastic particles and machine-made sand, wherein the plastic particles are spherical structures with interconnected pores (the pores are distributed in a honeycomb shape) formed by plastic strips interlaced and wound with each other, and the porosity of the plastic particles is 5%.
[0043] Specifically, the water reducer in this embodiment is polycarboxylate water reducer, and its dosage is 7.5kg / m 3 The thickener is industrial grade polyacrylamide (molecular weight 1.2×10 7 ), the dosage is 0.02kg / m 3 The quick-setting agent is AJ type quick-setting agent, and its dosage is 34.16kg / m 3 ; Cement content 450kg / m 3 , water content 175g / m 3 In this embodiment, the total amount of coarse aggregate and fine aggregate is 1780kg / m 3 , the mass ratio of fine aggregate to coarse aggregate is 51:49, and the fine aggregate includes particles with a particle size of less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm, and the mass ratio of fine aggregates with a particle size of less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm is 3:5:2. Among them, the fine aggregate with a particle size of 2mm-5mm is machine-made sand, and the fine aggregate with a particle size of less than 0.5mm and 0.5mm-2mm is a mixture of plastic particles and machine-made sand, and the addition amount of plastic particles with a particle size of less than 0.5mm accounts for 7% of the total amount of fine aggregate, and the addition amount of plastic particles with a particle size of 0.5mm-2mm accounts for 5% of the total amount of fine aggregate.
[0044] The preparation method of shotcrete of this embodiment, according to the particle size gradation defects of recycled coarse aggregate and machine-made sand, additionally add some plastic particles with a particle size of less than 0.5mm and a particle size of 0.5mm-2mm as fine aggregate, mix and stir all the raw materials together, the stirring time is not less than 3 minutes, and the cement slurry is filled into the plastic particles during stirring, so that the plastic particles and concrete form a whole, and finally the waste plastic recycled shotcrete of this embodiment is obtained. The 1-day compressive strength of the concrete obtained in this embodiment is 36Mpa, and the 28-day compressive strength is 68MPa.
[0045] Example 5
[0046] The waste plastic recycled shotcrete of this embodiment has the same raw material composition as that of embodiment 4, except that the amount of water reducer in this embodiment is 7.0 kg / m 3 The dosage of thickener is 0.01kg / m 3 , cement content 415kg / m 3 , water content 180kg / m 3 The dosage of the accelerating agent is 38kg / m 3 .
[0047] In addition, the total amount of coarse aggregate and fine aggregate in this embodiment is 1760 kg / m 3 The mass proportion of fine aggregate is 48%, and the fine aggregate with a particle size less than 0.5mm and a particle size of 2mm-5mm are all machine-made sand, and their mass proportions (relative to the total amount of fine aggregate) are 30% and 25% respectively. The fine aggregate with a particle size of 0.5mm-2mm is a mixture of machine-made sand and plastic particles in a mass ratio of 2:1.
[0048] The preparation method of the shotcrete of this embodiment is to mix and stir the raw materials evenly for not less than 3 minutes, so that the cement slurry is filled into the plastic particles during stirring, so that the plastic particles and the concrete form a whole, and finally the waste plastic recycled shotcrete of this embodiment is obtained. The one-day compressive strength of the concrete obtained in this embodiment is 27Mpa, and the 28-day compressive strength is 53MPa.
[0049] Example 6
[0050] The waste plastic recycled shotcrete of this embodiment has the same raw material composition as that of embodiment 4, except that the amount of water reducer in this embodiment is 7.4 kg / m 3 The dosage of thickener is 0.03kg / m 3 , cement content 460kg / m 3 , water content 175kg / m 3 The dosage of the accelerating agent is 30kg / m 3 .
[0051] In addition, the total amount of coarse aggregate and fine aggregate in this embodiment is 1728 kg / m 3 The mass proportion of fine aggregate is 53%, and the coarse aggregate is composed of recycled coarse aggregate and plastic particles in a mass ratio of 4:1. The mass ratio of fine aggregate with particle size less than 0.5mm, particle size between 0.5mm-2mm and particle size between 2mm-5mm is 3:5:2. Among them, fine aggregate with particle size less than 0.5mm and particle size between 0.5mm-2mm are all made of machine-made sand, and fine aggregate with particle size between 2mm-5mm is composed of plastic particles and machine-made sand in a mass ratio of 1:1.
[0052] In the preparation method of the shotcrete of this embodiment, plastic particles are additionally added as part of the coarse aggregate and part of the fine aggregate, and the raw materials are mixed and stirred evenly for not less than 3 minutes, so that the cement slurry is filled into the plastic particles during stirring, so that the plastic particles and the concrete form a whole, and finally the waste plastic recycled shotcrete of this embodiment is obtained. The one-day compressive strength of the concrete obtained in this embodiment is 25Mpa, and the 28-day compressive strength is 40MPa.
[0053] Example 7
[0054] The waste plastic recycled shotcrete of this embodiment has a raw material composition that is basically the same as that of Embodiment 6, with the main difference being that the coarse aggregate in this embodiment is composed of recycled coarse aggregate and plastic particles in a mass ratio of 9:1, and the concrete obtained in this embodiment has a 1-day compressive strength of 30 MPa and a 28-day compressive strength of 49 MPa.
[0055] Comparative Example 1
[0056] The waste plastic recycled shotcrete in this comparative example has the same raw material composition and proportion as Example 2, with the main difference being that the plastic particles in this example are obtained by directly crushing the waste plastics. The one-day compressive strength of the concrete in this comparative example is 20 MPa, and the 28-day compressive strength is 33 MPa. The directly crushed plastic particles have many edges and corners on the surface, which is not conducive to the strength of the concrete.
[0057] Comparative Example 2
[0058] The waste plastic recycled shotcrete of this comparative example has the same raw material composition and proportion as Example 2, with the main difference being that the porosity of the plastic particles in this comparative example is 35%, the 1-day compressive strength of the concrete in this comparative example is 22 MPa, and the 28-day compressive strength is 35 MPa, and the porosity of the plastic particles is too high, and a large amount of cement slurry is stirred to combine with the plastic particles to reduce the free slurry, resulting in reduced fluidity of the freshly mixed concrete.
[0059] Comparative Example 3
[0060] The waste plastic recycled shotcrete in this comparative example has the same raw material composition and proportion as Example 2, with the main difference being that the porosity of the plastic particles in this comparative example is 2%. Since the porosity of the plastic particles is too low, it is difficult for the cement slurry to combine with the plastic particles. Compared with Example 2, the bonding effect between the plastic particles in this comparative example and the cement product is poor, resulting in reduced concrete strength.
[0061] Comparative Example 4
[0062] The waste plastic recycled shotcrete in this comparative example is different from Example 2 mainly in that: in this comparative example, no additional plastic particles are added as fine aggregates. The one-day compressive strength of the concrete in this comparative example is 23Mpa, and the 28-day compressive strength is 37Mpa.
[0063] Comparative Example 5
[0064] The waste plastic recycled shotcrete in this comparative example is different from Example 2 mainly in that the mass of the plastic particles in this comparative example accounts for 30% of the total amount of fine aggregate, the one-day compressive strength of the concrete in this comparative example is 19 MPa, and the 28-day compressive strength is 32 MPa. If the amount of plastic particles added to the fine aggregate is too high, the overall strength of the concrete will be reduced too much.
[0065] Comparative Example 6
[0066] The waste plastic recycled shotcrete in this comparative example is different from Example 2 mainly in that the amount of water reducing agent in this comparative example is 8.2 kg / m 3 The dosage of thickener is 0.05kg / m 3 Due to the unreasonable addition amount of water reducer and thickener, the fluidity of the obtained concrete is relatively poor, and the 1-day compressive strength of the concrete obtained in this comparative example is 18 MPa, and the 28-day compressive strength is 30 MPa.
[0067] Comparative Example 7
[0068] The waste plastic recycled shotcrete in this comparative example is different from Example 2 mainly in that the thickener in this comparative example adopts 2-hydroxyethyl cellulose ether. Compared with Example 2, the plastic particles in this comparative example are unevenly distributed in the concrete and float in the concrete, resulting in the 1-day compressive strength of the obtained concrete being 29 MPa and the 28-day compressive strength being 38 MPa.
Claims
1. A waste plastic recycled shotcrete, characterized in that: The raw materials include cement, coarse aggregate and fine aggregate, wherein the fine aggregate part uses plastic granules, which are hollow structures with interconnected pores formed by plastic strips, and the pores connect the outside of the granules with the inside.
2. The waste plastic recycled shotcrete according to claim 1, characterized in that: The mass of the plastic particles in the fine aggregate accounts for 10% to 20% of the total amount of the fine aggregate; and / or the porosity of the plastic particles reaches 5% to 20%.
3. The waste plastic recycled shotcrete according to claim 2 is characterized in that: The plastic granules are a multi-layer stacked hollow structure formed by a plurality of plastic strips in an overall wavy shape, or a porous spherical structure formed by plastic strips interlaced and wound with each other.
4. The waste plastic recycled shotcrete according to any one of claims 1 to 3, characterized in that: The particle size of the coarse aggregate is 5mm-10mm, and the fine aggregate includes particles with a particle size less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm, and the mass proportions of the fine aggregate with a particle size less than 0.5mm, a particle size of 0.5mm-2mm, and a particle size of 2mm-5mm are 30%-35%, 45%-50%, and 20%-25%, respectively.
5. The waste plastic recycled shotcrete according to claim 4, characterized in that: The cement is ordinary silicate cement, and its dosage is 400-500 kg / m 3 ; and / or The concrete is also added with a water reducing agent, the dosage of which is 6.8 kg / m 3 ~7.8kg / m 3 ; and / or The concrete is also added with a thickener in an amount of 0.01 kg / m 3 ~0.03kg / m 3 ; and / or The concrete is also added with an accelerating agent, the dosage of which is 30-38 kg / m 3 ; and / or The water content in the concrete is 150-200 kg / m 3 ; and / or The total amount of coarse aggregate and fine aggregate in the concrete is 1700-1800 kg / m 3 , and the mass of fine aggregate accounts for 45% to 55% of the total aggregate.
6. The waste plastic recycled shotcrete according to claim 4, characterized in that: The fine aggregate comprises plastic particles and machine-made sand, and the addition amount and particle size distribution of the plastic particles are determined according to the grading defects of the recycled coarse aggregate and the machine-made sand.
7. The waste plastic recycled shotcrete according to claim 6, characterized in that: The coarse aggregate is recycled coarse aggregate, or a mixture of recycled coarse aggregate and plastic particles.
8. The waste plastic recycled shotcrete according to claim 4, characterized in that: The one-day compressive strength of the concrete is 25-37Mpa, and the 28-day compressive strength is 40-70Mpa.
9. A method for preparing waste plastic recycled shotcrete as claimed in any one of claims 1 to 8, characterized in that: include: The raw materials including cement, coarse aggregate and fine aggregate are stirred and mixed evenly in water. During the stirring process, the cement slurry is filled into the pores of the plastic particles, so that the plastic particles and the concrete form a whole.
10. The method for preparing waste plastic recycled shotcrete according to claim 9, characterized in that: The coarse aggregate comprises recycled coarse aggregate and plastic particles, and the mass ratio of the recycled coarse aggregate to the plastic particles in the coarse aggregate is (4-9):1.
Citation Information
Patent Citations
High-strength anti-crack concrete and preparation method thereof
CN110950603A
Paving method of regenerated roadbed based on full utilization of solid waste
CN113430881A
Extruded plastic aggregate for concrete
CN113683329A
Regenerated plastic particles capable of preventing materials from being stuck
CN218256112U
Synthetic aggregate for use in concrete
US8921463B1